2015
DOI: 10.1002/pros.22978
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of lipocalin 2 promotes cell migration and invasion through activating ERK signaling to increase SLUG expression in prostate cancer

Abstract: LCN2 plays an important role in promoting cell migration and invasion of prostate cancer by inducing EMT through the ERK/SLUG axis. Therefore, targeted inhibition of LCN2 may represent a therapeutic strategy to prevent the metastasis of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 49 publications
4
64
1
Order By: Relevance
“…NGAL is predictive of a poor prognosis in some cancers [73,91,105,134]. Ectopic NGAL expression enhanced positively the ability of prostate cancer cells to form colonies in soft agar; likewise, suppression of NGAL dramatically inhibited colony formation [91,105,134].…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…NGAL is predictive of a poor prognosis in some cancers [73,91,105,134]. Ectopic NGAL expression enhanced positively the ability of prostate cancer cells to form colonies in soft agar; likewise, suppression of NGAL dramatically inhibited colony formation [91,105,134].…”
mentioning
confidence: 97%
“…NGAL is considered by some scientists to have properties of an oncogene, or in some cases, a tumor suppressor gene [9,10,73,89,96,[127][128][129][130][131][132][133][134]. Increased levels of NGAL have been detected in the urine and plasma of patients with various types of cancer (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…60 LCN2 plays an important role in promoting cell migration and invasion in cooperation with MMP-9 and by inducing EMT through the ERK/SLUG axis. 61 Growth differentiation factor 15 (GDF-15/MIC-1) belongs to the TGF-b superfamily and regulates inflammatory and apoptotic pathways in inflammation, cancer and obesity and was associated with aberrant growth and a poor prognosis. 62,63 Incubation of blood monocytederived macrophages with CM of an esophageal squamous cell carcinomas cell line induced M2 polarization and overexpression of GDF-15 as well as IL-6 and IL-8.…”
Section: Secretory Phenotype Of Sclc Ctc-induced Macrophagesmentioning
confidence: 99%
“…Interestingly, proteins encoded by all three Nudt3 target mRNAs have been implicated in increased tumor cell invasion and metastatic potential. The expression of LCN2 is elevated in numerous human epithelial cancers, including breast (Lim et al 2007), and shown to promote cell migration and invasion (Fougere et al 2010;Ding et al 2015). Whether the function of Nudt3 in modulating cell motility is a contributing factor in cellular invasion and metastasis remains to be determined.…”
Section: Discussionmentioning
confidence: 99%